Etika Penggunaan Media Social dalam Perspektif Hadis Studi Tentang Privasi dan Tanggung Jawab Social - Zaid Almubarok Simangunsong; Ferizal Ferizal (Jurnal Budi Pekerti Agama Islam, 2025)
This study examines the ethics of social media use from the perspective of hadith and verses of the Qur'an with a focus on privacy and social responsibility. Social media, as a dominant communication tool, is often misused, resulting in privacy violations, the spread of inaccurate information, and other negative impacts. This study uses a literature approach to authentic hadiths and interpretations of verses of the Qur'an. The results of the study show that Islam prohibits the actions of tajasuss (spying) and ghibah (backbiting), as emphasized in the hadith: "Whoever spies on others, Allah will spy on him." In addition, QS. Al-Isra: 36 reminds us of the importance of verifying information before it is disseminated. The principle of amar ma'ruf nahi munkar requires social media users to encourage goodness, share positive content, and avoid destructive behavior, such as bullying or the spread of inappropriate content. The application of Islamic ethics in social media can reduce the negative impacts of technology while creating safer and more beneficial interactions in cyberspace.